AN IMPROVEMENT IN THE MOBILITY OF MANGKUBUMI YOGYAKARTA AREA WITH URBAN MODELING INTERFACE SIMULATION - FA Galih Sih Hartanta; Arif Kusumawanto (ASEAN Journal of Systems Engineering, 2020)
Mangkubumi Yogyakarta area is not only a strategic area in the city of Yogyakarta, which lies on the axis of philosophy, forming the spatial structure of the city of Yogyakarta but also a compact area with building facilities that function as offices, education, trade/services, worship, and settlements. The discourse of developing the site has long been announced as a supporting area for Malioboro tourism, and Tugu station developed into TOD (Transit Oriented Development), among others. In 2019, the research, development research aiming to find an area model supporting the realization of the maximum mobility value was carried out in Mangkubumi area to measure mobility levels in the area, and the results of this study found that the rate of mobility and walkability was 76 and 79 respectively.The method used was a simulation of the Urban Modeling Interface (UMI) software to measure the value of mobility in regional models. The research step used area modeling, which was carried out in eight models. After the simulation, the best model with the highest mobility value was selected. The eight models were made based on the four road network patterns of Morlok’s idea (Grid, Spiral, Hexagonal, and Delta), each of which was designed to be two types, namely, type A and type B. Type A was a form of modeling by conducting interventions focused on residential building facilities, and type B was focused on all area building facilities. The finding of this research was that the best road network pattern was the Delta network pattern after intervening in all building facilities and after carrying out land use by placing residential building facilities at the center of the area and placing other building facilities on edge the area. This simulation resulted in a walkability score of 92 and bike-ability of 92. The score is the highest in the walk score ranking level. A value of 92 means that there are walker's paradise, daily business not requiring a car, and biker's paradise, daily affairs done by cycling.